Predicting Time-to-Failure of Red Sandstone by Temporal Precursor of Acoustic Emission Signals - Ansen Gao; Chengzhi Qi; Renliang Shan; Chunlai Wang (Geofluids)
The evolution pattern of rock damage is a progressive failure process of rock materials. It is the basis for predicting failure time of rock materials. By theoretical and experimental analysis, the acoustic emission (AE) precursor characteristics of rock fracture and the gradual evolution pattern of rock damage were analyzed detailedly. Then, the time-to-failure of red sandstone was predicted and compared by several different methods. The results demonstrated that the failure process of red sandstone can be divided into the stable deformation stage and the critical acceleration failure stage. In the critical acceleration failure stage, the AE precursor of rock failure was easy to be observed, and the AE event rate occurred as jump-like increase phenomenon. Moreover, the gradual evolution pattern of rock damage obeyed an exponential function, and the damage acceleration phenomenon existed in the critical failure stage. Furthermore, the higher values of the average of rock damage was, the more obvious linear evolution pattern will be, which was beneficial to improve the prediction accuracy of time-to-failure of rocks. Clearly, the linear prediction results of rock failure time, after taking average values of five rock damage variables, had more higher accuracy when damage variable exceeded D=0.5. The predicting result of specimen R1 was 0.2 s ahead of its actual failure time, and the predicting result of specimen R6 was 8.1 s ahead of its actual failure time. Therefore, this method is meaningful and it can be used for the early warning of rockburst.